"No CAP": Reflections on the Intersectionality, Positionality and the Experiences of Navigating Race as a Black Male Criminologist. (July 2021) - Richardson, Joseph
The arrest of respected Black professor and scholar Henry Louis Gates, Jr., by the Cambridge Police Department in 2009 for allegedly breaking into his own home proverbially "set the table" for this discussion. Following his arrest, Gates noted: "There are one million black men in jail in this country and last Thursday I was one of them. This is outrageous and this is how poor black men across the country are treated every day in the criminal justice system. It's one thing to write about it, but altogether another to experience it." Regardless of social class or occupational prestige, Black professors at predominately White institutions are subjected to hyper-surveillance and racially bias policing in public spaces on campus. Using intersectionality and positionality as conceptual frameworks, this paper describes the lived experiences of a Black professor and criminologist at a predominately White institution and his encounters with the university's police department and the carceral state. Using Armour's (2020) N*gga Theory, which is framed by Critical Race Theory, I analyze the relationship between race, class, unequal justice, and the politics of respectability. I use Armour's N*gga Theory (2020) to show solidarity between those vilified as a "crime prone" Black underclass, and the less "crime prone" Black bourgeoisie. Although, the Black bourgeoisie in the academy may embrace the politics of respectability, according to N*gga Theory there is no moral or political distinction between the those considered good Negroes and those considered bad.